How Differences in Property Taxes within Cities Affect Urban Sprawl? - Yan Song; Yves Zenou (Research Institute of Industrial Economics (IFN), 2008)
This article attempts a formal analysis of the connection between the differentiated property tax rates within urban areas and urban spatial pattern in U.S. cities. We first develop a duocentric-city model where the Central Business District (CBD) is located at the origin while the Suburban Business District (SBD) is at the other end of the city. We show that the ratio between the property tax in the suburbs and in the center has an ambiguous impact on the size of the city. We then test this model empirically to determine this sign by using a dataset of effective property tax rates we developed using GIS techniques for central cities and suburbs in 445 urbanized areas. The empirical analysis estimates the link between these two variables by controlling for variables such as population, income, agricultural rent, commuting cost, climate, crime, and employment structure. Results from the empirical analyses suggest that a lower property tax rate in the suburbs in comparison to the central city is associated with more expansive urban growth and greater level of decentralization of population and employment.
Keywords: H30; H71; R14; 330; Central City; Suburbs; Urban Sprawl; Urban Decentralization; Differentiated Property Tax; Vermögensteuer; Urbanisierung; Stadtgröße; Stadtzentrum; Stadtteil; USA